Bicarbonate enhanced heterogeneous activation of peroxymonosulfate by copper ferrite nanoparticles for the efficient degradation of refractory organic contaminants in water. (January 2023) - Cai, Chun; Liu, Yangfan; Xu, Rui; Zhou, Jiaheng; Zhang, Jin; Chen, Yu; Liu, Lingyu; Zhang, Lexiang; Kang, Shuping; Xie, Xianjun
Abstract: Nowadays, the treatment of residual refractory organic contaminants (ROCs) is a huge challenge for environmental remediation. In this study, a potential process is provided by copper ferrite catalyst (CuFe2 O4 ) activated peroxymonosulfate (PMS, HSO5 − ) in the bicarbonate (HCO3 − ) enhanced system for efficient removal of Acid Orange 7 (AO7), 2, 4-dichlorophenol, phenol and methyl orange (MO) in water. The impact of key reaction parameters, water quality components, main reactive oxygen species (ROS), probable degradation mechanism, rational degradation pathways and catalyst stability were systematically investigated. A 95.0% AO7 (C0  = 100 mg L −1 ) removal was achieved at initial pH (pH0 ) of 5.9 ± 0.1 (natural pH), CuFe2 O4 dosage of 0.15 g L −1, PMS concentration of 0.98 mM, HCO3 − concentration of 2 mM, and reaction time of 30 min. Both sulfate radical (SO4 − ) and hydroxyl radical ( OH) on the surface of catalyst were proved as the predominant radical species through radical quenching experiments and electron paramagnetic resonance (EPR) analysis. The buffer nature of HCO3 − was partially contributed for the enhanced degradation of AO7 under CuFe2 O4 /PMS/HCO3 − system. Importantly, according to 13 C nuclear magnetic resonance (NMR) and EPR analysis, the positive effect of bicarbonate may be mainly attributed to the formation of peroxymonocarbonate (HCO4 − ), which may enhance the generation of OH. The magnetic CuFe2 O4 particles can be well recycled and the leaching concentration of Cu was acceptable (<1 mg L −1 ). Considering the widespread presence of bicarbonate in water environment, this work may provide a safe, efficient, and sustainable technique for the elimination of ROCs from practical complex wastewater. Graphical abstract: Image 1 Highlights: CuFe2 O4 was prepared and used in a HCO3 − enhanced heterogeneous PMS process. HCO3 − could be transformed to HCO4 − by reaction with PMS. Possible reaction mechanism in the CuFe2 O4 /PMS/HCO3 − process was studied in details. AO7 intermediates were identified and a probable degradation pathway was proposed. The application and practicality of CuFe2 O4 /PMS/HCO3 − process was evaluated.